Narcotrafic and Mexican journalists: Challenges in the line of duty according to profesional life cycle - Gutiérrez Leyton, Alma Elena; Torres Herrera, Moisés
Mexico has been classified as one of the most dangerous countries in the world for the exercise of journalism. In spite of national and international organizations’ attempts to promote an environment that protects the freedom of the press, the self-censorship and aggressions have continued. This has been partially accredited to the violence derived from drug related activities and divergent political ideologies. As Mexico continues on its road to a stronger democracy, it is increasingly important to understand the challenges that the journalist experience on a daily basis. In light of the importance of the role of the journalist in a democratic society, the purpose of this study is to identify the challenges that Mexican journalists currently face through a series of case studies of journalists with activities in Monterrey, Mexico. In doing so it provides an inside look at how public policy, the justice system, organized crime networks and corruption, among others, affect the exercise of journalism in a particular society. Based on previous authors’ work that identifies and classifies the barriers to effective media development in Latin America, this study provides a personal account of the challenges that journalists in Mexico face in the line of duty. Keywords: journalism and drug violence, new professional challenges, professional life cycles